Preparation of p-type Fe2O3 nanoarray and its performance as photocathode for photoelectrochemical water splitting - Xiaoli Fan; Fei Zhu; Zeyi Wang; Xi Wang; Yi Zou; Bin Gao; Li Song; Jianping He; Tao Wang (Frontiers in Chemistry)
Photoelectrochemical (PEC) water splitting has the potential to convert solar energy into chemical energy, emerging as a promising alternative to fossil fuel combustion. In PEC systems, p-type semiconductors are particularly noteworthy for their ability to directly produce hydrogen. In this work, Fe2O3 with p-type semiconductor properties grown directly on the conductive glass substrate were successfully synthesized through a simple one-step hydrothermal method. The analysis results indicate that the Fe2O3 exhibits a spindle shaped nanoarray structure and possesses a small band gap, thereby demonstrating excellent photoelectrochemical performance as a photocathode with photocurrent density of −23 μA cm−2 at 0.4 V vs. RHE. Further band structure tests reveal that its conduction band position is more negative compared to the hydrogen evolution potential, highlighting its significant potential as a photocathode material.